The Influence of Religiusity, Beliefs and Digital Literacy of Muzakki's Interests Paying Zakat through Fintech - Lailatis Syarifah; Achmad Otong Bushtomi; Moh Mabruri Faoz (Pusat Publikasi Nusantara, 2022)
The collection of zakat funds with zakat potential in Indonesia has not been maximized, because there are still many muzakki who do not distribute their zakat through amil zakat institutions due to several factors. The development of the current digital era makes it easy for muzakki to pay their zakat through digital channels with the help of financial technology. The purpose of this study was to determine the effect of religiosity, trust and digital literacy on muzakki's interest in paying zakat through fintech. This study uses a quantitative approach. Data obtained from the distribution of questionnaires. The data obtained were analyzed using validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, linearity test, multiple linear regression test, t test, F test, and coefficient of determination test. The results of this study are that the religiosity variable has no significant effect on muzakki's interest in paying zakat through fintech as evidenced by the t arithmetic value < from t table which is 0.741 smaller than t table 1.66159 and sig value (0.460) > 0.05. The trust variable has a positive and significant effect on the interest of muzakki to pay zakat through fintech as evidenced by the value of t count > t table which is 6.003 greater than 1.66159 and the value of sig (0.000) <0.05. The digital literacy variable has a positive and significant effect on muzakki's interest in paying zakat through fintech as evidenced by the t count > t table, which is 2.14 greater than1.66159 and the value of sig (0.012) <0.05. Then the variables of religiosity, trust and digital literacy together have a significant effect on muzakki's interest in paying zakat through fintech with the results of F arithmetic > F table, namely 29.9006 > 2.14 and sig value of 0.000 <0.05.